Konsumsi dan kecernaan protein kasar dan serat kasar sapi bali jantan sapihan yang disuplementasi pakan konsentrat kulit pisang terfermentasi - Alxen Mefi Boset Umbu Dassa; Yohanis Umbu Laiya Sobang; Marthen Yunus (Jurnal Peternakan Lahan Kering, 2019)
The aim of this study was asses the effect of concentrate level containing banana peel fermented on intake and digestibility of crude protein and crude fiber on male Bali cattle. Three male cattle were used in this study following Latin square Design (LSD) (4x4), consisted of 4 treatments and 4 periods as replication. The three treatment were P0 = local feeds consisted of (Leucaenaleucocephala) as commonly used by local farmers + 1kg concentrate without fermented banana peel, P1 = local feeds as commonly used by local farmers + 1 kg concentrate contains 10% banana peel fermented, P2 = local feeds as commonly used by local farmers + 1 kg concentrate contains 20% banana peel, P3 = local feeds as commonly used by local farmers + 1 kg concentrate contains 30% banana peel fermented. Data collected were subjected to Analysis of variance (ANOVA) procedure.The research result that the treatmant was significant effect (P<0.05) on crude protein and crude fiber but not significant (P>0.05) on crude protein and crude fiber digestible. Conclusion of this research is improving to intake and digestible crude protein and crude fiber ration male Bali cattle with added 20% ferment banana peel.